Macrosiphoniella madeirensis Aguiar & Ilharco sp. nov. (Hemiptera: Sternorrhyncha: Aphididae) from Madeira Island - Aguiar, A. M. Franquinho; Ilharco, Fernando Albano (Zootaxa, 2005)
A new species of the aphid genus Macrosiphoniella del Guercio (M. madeirensis sp. nov.) is described from material collected on Helichrysum melaleucum in Madeira Island. Macrosiphoniella helichrysi Remaudière is redescribed.